Karakteristik Pelayanan Gembala Jemaat Menurut 1 Petrus 5:1-4 dan Implementasinya Bagi GPdI Zion Altar Malang - Tedjo, Petter; Heryanto, Doni (Jurnal Teologi dan Pelayanan Kerusso, 2024)
The characteristics of effective pastoral service, as outlined in 1 Peter 5:1-4, entail that pastors are expected to serve as role models for the congregation. Peter expresses hope that these shepherds will be good leaders for the existing flock. Rather than following behind their sheep, pastors are to lead them. The objective of this research is to enable congregation leaders at the Pentecostal Church in Indonesia Zion Altar Malang (hereafter referred to as GPdI Zion Altar Malang) to implement the service characteristics of pastoral care according to 1 Peter 5:1-4. This is prompted by the suboptimal nature of the service characteristics of pastors in their oversight of local churches. The research, conducted using qualitative methods, involved data collection from several participants, including pastors and supporting servants involved in pastoral care at GPdI Zion Altar Malang. The findings of the research revealed issues such as poorly organized financial management, suboptimal implementation of teaching programs, and exacerbated by the absence of counselling services for congregation members grappling with issues in their faith journey. Pastors acknowledge the necessity of enhancing competency to realize the characteristics of pastoral care in accordance with God’s Word, particularly as outlined in 1 Peter 5:1-4, for the spiritual growth of congregation members.